Meningkatkan Kesadaran Masyarakat Mengenai Kerelawanan Tanggap Bencana Dan Protokol Kesehatan Dimasa Pandemi - Siti Hamidah; Sri Hidayah; Cindy Yuliastara; Muhammadi Dimas Yanuar; Yustikarina; Agustiani; Nur Jannah; Hatmawati; Sellawati (Wadah Inovasi Indonesia, 2021)
The flood disaster that hit Kabupaten Banjar in early 2021 maded these area got disaster alert status. The flood disaster struck and also coincided with the Covid-19 pandemic disaster made people affected by floods aware of the importance of disaster mitigation and also the importance of a village being prepared to face possible disasters. KKN-Tematik Fisip ULM which carries the theme